Crop Production Allocations for Saving Water and Improving Calorie Supply in China - Liu, Yilin; Zhuo, La; Yang, Xi; Ji, Xiangxiang; Yue, Zhiwei; Zhao, Danyue; Wu, Pute (Frontiers in Sustainable Food Systems, 2021)
The limited available water resources and competition among different water use sectors have become the main constraints of food security and sustainability. Faced with the inability to expand the area of cultivated land due to urbanization and population growth, one of the biggest challenges and risks for developing countries is to ensure the supply of food quantity and quality under extremely limited water resources. To achieve water-saving and improve calorie supply by adjusting crop production allocations, three objectives—of minimum blue water footprint, maximum calorie production, and each crop production no less than the reference level of nine main crops in China—were achieved using a non-dominated sorting genetic algorithm II. The results display that compared with the reference year, model Maize+ (maize production increased) had significant blue water saving ( 32%), the blue water footprint of crop production in all provinces reduced, and its calorie production increased by 4%. This solution is not realistic for China because wheat and rice production need to be reduced by 82 and 80%, respectively. However, model Citrus– (citrus production decreased) reduced the blue water footprint of crop production ( 16%), and increased calorie production ( 12%). Compared with other solutions, it is a sustainable crop production structure that is easier to realize because it is better at meeting the production of each crop. Therefore, China can appropriately increase the planting area of maize and reduce the planting of citrus and other crops that consume more blue water and produce fewer calories to ensure the security and sustainability of food supplies. However, the improvement of water saving-technology, rationalization of agricultural water resources management, crop production allocations mentioned in this study, and other efforts are necessary to achieve this goal.